Dependence on external finance: an inherent industry characteristic? - Ulf von Kalckreuth; George M. von Furstenberg (Deutsche Bundesbank, 2006)
Rajan and Zingales (1998) use U.S. Compustat firm data for the 1980s to obtain measures of manufacturing sectors? Dependence on External Finance (DEF). They take any differences in these measures to be structural/technological and thus applicable to other countries. Their joint assumptions about how to obtain representative values of DEF by sector and about why these values differ fundamentally between sectors have been adopted in additional studies seeking to show that sectors benefit unequally from a country?s level of financial development. However, the assumptions as such have not been examined. The present study, conducted with cyclically adjusted annual measures of DEF derived from U.S. industry data for 1977-1997, attempts to do so using data that are aggregated by sector. We find that those variables that may be regarded as structural/ technological have very low explanatory power, and that the DEF figures calculated from micro data do not correspond closely to what is obtained from aggregate figures. Hence key assumptions on which RZ's argumentation is based could not be validated.
Keywords: G20; O16; O14; E50; G30; 330; Growth and finance; financial development; industry structure; Fremdkapital; Verarbeitendes Gewerbe; Branche; Finanzsektor; Wirtschaftswachstum; Schätzung; USA